Non-typhoidal salmonella sepsis with severe small bowel diarrhoea and acute kidney injury in an immunocompetent patient - Devadas, Mahesh; Joseph, Rajesh; Thomas, ET Arun (Indian Journal of Case Reports, 2020)
Non-typhoidal salmonella serovars mainly cause enteric infection, but it can also rarely cause invasive infections.These invasive infections are mostly seen in immunocompromised subjects. We are reporting a case of non-typhoidal salmonella sepsis in a 60 year old individual. He presented with severe small bowel diarrhoea mimicking cholera. Blood cultures grew Salmonella enteritidis. He had severe acute kidney injury requiring hemodialysis. The clinical course was protracted with diarrhoea subsiding only after 12 days. He was treated with two weeks of intravenous ceftriaxone.